Vincent Van Gogh : The complete paintings - Walther, Ingo F.; Metzger, Rainer; Gogh, Vincent van, 1853-1890. (Köln ; London : Taschen, 2001)
Vincent van Gogh is regarded not only as a major pioneer of modernism, but as one of the greatest artists of all time. This book combines a detailed monograph on his life and art with a complete catalogue of his paintings.
This ed. of this translation originally published:1997.
Includes bibliographical references (p. 721-725) and index.
Translated from the German.
Keywords: Gogh, Vincent van, -- 1853-1890 -- Criticism and interpretation; Art and Design